2023
DOI: 10.1109/tnsre.2022.3225759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dyadic Haptic Collaboration on Ankle Motor Learning and Task Performance

Abstract: Optimizing skill acquisition during novel motor tasks and regaining lost motor functions have been the interest of many researchers over the past few decades. One approach shown to accelerate motor learning involves haptically coupling two individuals through robotic interfaces. Studies have shown that an individual's solo performance during upper-limb tracking tasks may improve after haptically-coupled training with a partner. In this study, our goal was to investigate whether these findings can be translated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…1A). (1) In blocks with soft connections, the stiffness (K virt ) and damping (C virt ) were set to 20 Nm/rad and 2 Nm•s/rad, respectively, consistent with our previous study [12]. (2) In blocks with hard connections, the stiffness and damping were set to 200 Nm/rad and 6.3 Nm•s/rad, respectively.…”
Section: B Experimental Protocolmentioning
confidence: 76%
See 4 more Smart Citations
“…1A). (1) In blocks with soft connections, the stiffness (K virt ) and damping (C virt ) were set to 20 Nm/rad and 2 Nm•s/rad, respectively, consistent with our previous study [12]. (2) In blocks with hard connections, the stiffness and damping were set to 200 Nm/rad and 6.3 Nm•s/rad, respectively.…”
Section: B Experimental Protocolmentioning
confidence: 76%
“…Simulating the connection as a system of springs in series suggested that improvements in tracking could be explained by the averaging of random errors within each dyad, depending on the stiffness of the connection and the relative ankle stiffness of each partner. One potential explanation for these results is the relatively soft stiffness of the connection used in our previous work [12], possibly limiting the communication of tracking goals as described by Takagi et al [5].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations